2022
DOI: 10.1289/ehp9467
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs, Polychlorinated Biphenyls, and Environmental Liver Disease in the Anniston Community Health Survey

Abstract: Background: Polychlorinated biphenyl (PCB) exposures have been associated with liver injury in human cohorts, and steatohepatitis with liver necrosis in model systems. MicroRNAs (miRs) maintain cellular homeostasis and may regulate the response to environmental stress. Objectives: We tested the hypothesis that specific miRs are associated with liver disease and PCB exposures in a residential cohort. Methods: Sixty-eight targeted hepatotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 57 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…These environmental chemicals include distinct categories of contaminants such as persistent organic pollutants (POPs) like polychlorinated biphenyls (PCBs). Using epidemiologic data and experimental animal models, several studies have demonstrated that exposure to PCBs is associated with liver injury, steatohepatitis, and obesity (Cave et al, 2022; Clair et al, 2018; Deng et al, 2019). Irrespective of etiology, each subtype of FLD can further progress to more severe pathological states, which are dictated by other factors including sex, diet, alcohol or tobacco use, and genetic susceptibility (Crabb et al, 2020; Younossi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These environmental chemicals include distinct categories of contaminants such as persistent organic pollutants (POPs) like polychlorinated biphenyls (PCBs). Using epidemiologic data and experimental animal models, several studies have demonstrated that exposure to PCBs is associated with liver injury, steatohepatitis, and obesity (Cave et al, 2022; Clair et al, 2018; Deng et al, 2019). Irrespective of etiology, each subtype of FLD can further progress to more severe pathological states, which are dictated by other factors including sex, diet, alcohol or tobacco use, and genetic susceptibility (Crabb et al, 2020; Younossi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, PCB exposures have been associated with human hepatocellular carcinoma development (46,50). Intriguingly, pathway enrichment analysis and liquid liver biopsy generated from the differentially expressed circulating microRNAs associated with PCB exposures in the ACHS population demonstrated activation of hepatocellular carcinoma-associated pathways involving the tumor suppressor P53 (3). Overall, the mechanisms responsible for the observed PCB-associated hepatocellular carcinoma development in the current study, particularly focusing on carcinogenic pathways, are currently being investigated and findings will be disseminated in a separate publication.…”
Section: Discussionmentioning
confidence: 99%
“…Polychlorinated biphenyls (PCBs) are environmental toxicants associated with numerous health effects such as cardiovascular complications and metabolic diseases in exposed populations (1)(2)(3). Categorized as persistent organic pollutants (POPs), PCBs continue to threaten public health due to their resistance to degradation and bioaccumulation in living organisms (4).…”
Section: Introductionmentioning
confidence: 99%
“…One study found that in PCOS ovarian granulosa cells, inhibition of long noncoding RNA (lncRNA) plasmacytoma variant translocation 1 (PVT1) and overexpression of miR-17-5p resulted in the downregulation of phosphatase and tensin homolog (PTEN) and promoted cell proliferation, thereby inhibiting the apoptosis of ovarian granulosa cells (38). In addition, the downregulation of miR-99a expression in patients with PCOS may be closely related to insulin resistance and hyperinsulinemia (39). miR-99a can inhibit the proliferation of human glomerular basement membrane cells and promote their apoptosis by targeting insulin-like growth factor 1 receptor (IGF-1R), which may be part of the cause of abnormal PCOS follicles (40).…”
Section: Discussionmentioning
confidence: 99%